Environmental and Physiological Factors Associated With Stamina in Dogs Exercising in High Ambient Temperatures - Robbins, Patrick J.; Ramos, Meghan T.; Zanghi, Brian M.; Otto, Cynthia M. (Frontiers in Veterinary Science, 2017)
This IACUC approved study was performed to evaluate the environmental, physiological and hematological components that contribute to stamina following successive bouts of exercise that included searching (5-min), agility (5-min), and ball retrieve (<10-min). Regularly exercised dogs (N=12) were evaluated on 5 separate occasions. The population consisted of 8 males and 4 females ranging in age from 8-23 months, which included 6 Labrador retrievers, 3 German shepherds and one each English springer spaniel, German wirehaired pointer, and Dutch shepherd. The exercise period was up to 30 minutes with 5 minutes of intermittent rest between the exercise bouts or until a designated trainer determined that the dog appeared fatigued (e.g. curled tongue while panting, seeking shade, or voluntary reluctance to retrieve). At the end of the exercise period, pulse rate, core temperature, blood lactate, and venous blood gas were collected. The median outdoor temperature was 28.9°C (84°F) (IQR; 27.2-30°C/81-86°F) and median humidity was 47% (IQR; 40-57%). Median duration of exercise was 27 minutes (IQR; 25-29). No dog showed signs of heat stress that required medical intervention. The components used to measure stamina in this study were total activity, post-exercise core body temperature, and increase in core body temperature. When controlling for breed, total activity, as measured by omni-directional accelerometer device, could be predicted from a linear combination of the independent variables: pre-exercise activity (p=0.008), post-exercise activity (p<0.001), outdoor temperature (p=0.005), reduction in BEecf (p=0.044), and decrease in TCO2 (p=0.005). When controlling for breed and sex, increase in core body temperature could be predicted from a linear combination of the independent variables: study day (p=0.005), increase in PR (p<0.001), increase in lactate (p=0.001), reduction in BEecf (p=0.031), increase in glucose (p=0.044), increase in hematocrit (p=0.032), and increase in hemoglobin (p=0.038). This study suggests that the influence of outdoor temperature, pre- and post-exercise activity, and the metabolic parameters are important components of stamina associated with exertion.